Growth Patterns, Length-Weight Relationships, and Condition Factors of Bullet Tuna (Auxis rochei) from PPI Bias Lantang, Seraya Timur, Bali - Sinar Jayadi; I Wayan Restu Nuarsa; Nyoman Dati Pertami (Advances in Tropical Biodiversity and Environmental Sciences, 2025)
The growth pattern analysis using the length-weight relationship and condition factor of the bullet tuna (Auxis rochei) landed at PPI Bias Lantang, Seraya Timur, Bali, has not yet been determined. This study was conducted to determine the growth pattern using the length-weight relationship and the condition factor of bullet tuna. Fish samples were collected from March to May 2024, three times over three months, with intervals of three weeks. The methods used during the research were descriptive, quantitative, and simple random sampling. The bullet tuna fishing season starts in March and lasts until May. The fishing was conducted around the waters of the Bali-Lombok Strait. A total of 300 bullet tuna samples were obtained during the study. The length-weight relationship analysis revealed a positive allometric growth pattern for bullet tuna at PPI Bias Lantang, with a b value of 3.0308. The length-weight relationship shows a strong coefficient of determination with R² = 0.7468. The graph and equation illustrate the length-weight relationship for bullet tuna (Auxis rochei). The condition factor values of the bullet tuna ranged from 1.0048 to 1.0062, indicating that the body shape is relatively less slender.